If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+3)=4(2x-7)
We simplify the equation to the form, which is simple to understand
2(x+3)=4(2x-7)
Reorder the terms in parentheses
+(+2x+6)=4*(2x-7)
Remove unnecessary parentheses
+2x+6=+4+*(+2x-7+)
Reorder the terms in parentheses
+2x+6=+(+8x-28)
Remove unnecessary parentheses
+2x+6=+8x-28
We move all terms containing x to the left and all other terms to the right.
+2x-8x=-28-6
We simplify left and right side of the equation.
-6x=-34
We divide both sides of the equation by -6 to get x.
x=5.66666666667
| 2sin^2x+5sin^2x=3 | | 4x+12n=36 | | Ax+ca=b | | 4x+3(x+2)=13 | | xa+cx=b | | ax+xc=b | | xa+xc=b | | 4y-8=1+5y-36 | | Ax+cx=b | | 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= |